Evolution of the forms of expression of the authoral mode in the French novel - Smushchynska , Iryna (Current issues of Ukrainian linguistics: theory and practice, 2024)
The article is devoted to the problem of expressing the author's mode in artistic discourse, and specifically to the types of narrators and their change in French literature of the 19th-21st centuries. The main focus is on the internalized narrator as the leading form of the modern French novel, which receives a polymodal status due to the special contamination of the voices of the author, the narrator and the character.The article continues the development of the theory of textual modality, namely, the analysis of linguistic forms of its presentation in the text is made, the main means of expressing the modal meaning and showing the author's attitude are determined. Among them, the subjective epithet, the techniques of speech dislocation, and inserted elements that enhance the emotionality of the work deserve special attention.The evolution of the forms of presentation of the author's point of view, the linguistic personality of the author as a bearer of a certain culture is studied, the features of the new text structure with contaminated types of speech are highlighted. Attention is focused on the interconnectedness of the categories of modality, reference and axiologicality, their representation in different parts of the composition, as well as such categories as modalization and focalization, which are considered as meaning- and text-forming. Special attention is paid to expressive modality, forms of integral polylogue, subjective psychologism of the story. It turns out that a special role begins to be given to the mode of doubt, uncertainty of meaning, mechanisms of reflection, actualization of the communicative and discursive feature of the story, and subjective evaluation.It was found that the perceptive mode characteristic of the beginning of the story creates a split reference, to which the mode of subjective reflection is added. The assimilation of the author's voice to the character's voice leads to the disappearance of bright figurative forms, but the modality of accentuation and clarification appears. Modes of self-reflection, self-ignorance, contradictions to generally accepted stereotypes, the appearance of which was impossible in previous narrative types, deserve special attention.
Keywords: modality, author's mode, narrator, subjectivization, interiorized narrative, novel, French language.